Web Opera and Opera on the Web (Sound Stage Screen, 2023)
Introduction;Caroline Mounier-Vehier, Creating Opera for the Web: Au web ce soir – Ursule 1.1 and Actéon;Benjamin Lazar interviewed by Caroline Mounier-Vehier, Transposing the Necessity of the Present;Romeo Castellucci in conversation with Sofija Perović;Simon Hatab in conversation with Sofija Perovič;Julia Bullock in conversation with Sofija Perović.
Keywords: web opera; dramaturg; digital; internet; theater